School dropout in high school: a scientometrics analysis (Research, Society and Development, 2020)
The study aimed to identify and analyze, from a scientometric analysis, the academic productions related to school dropout in high school available on the website of the libraries of the five Federal Universities of RS, exploring in the search field, the thesis bank, dissertations and monographs available online and linked to the respective graduate programs based on the terms “dropout from Integrated High School”, “dropout form High School” and “dropout from school”. 193 publications were found, of which 11 monographs and four dissertations were selected according to the analytical matrix built for this investigation. The analysis considered the research objectives, methodologies, causes and solutions to avoid school dropout. It was identified that the most decisive causes for school dropout are low interest and study/work ratio; while the alternatives to reduce dropout are related to greater community participation and curricular adequacy. It is concluded that school dropout is multifactorial, pointing out the need to review the list of causes, their consequences and preventive actions. Thus, there is a lack of studies that can point to ways and alternatives to combat school drop-out based on scientific bases linked to graduate programs at Federal Universities in RS.